Understanding constraints to the transformation rate of global energy infrastructure. Issue 1 (8th May 2015) - Lane, Joe L.; Smart, Simon; Schmeda‐Lopez, Diego; Hoegh‐Guldberg, Ove; Garnett, Andrew; Greig, Chris; McFarland, Eric
Abstract : A massive transformation of the global energy supply system is required if deep reductions in atmospheric carbon dioxide emissions are to be achieved. A top–down review of historical data and energy forecasts provides a perspective on the magnitude of the challenge. Global engineering capability has expanded significantly over the last two decades, accommodating more than 100 GW/year increase in electricity generation infrastructure. However, business‐as‐usual demand forecasts to 2050 will require more than double the global rates of energy project execution. Transforming to a low‐carbon energy supply mix requires 30–70 GW/year of additional infrastructure, due to the increased reliance on intermittent renewables, and the earlier‐than‐expected replacement of existing coal power plants. Although all power systems share many similar subsystems that will need to be delivered regardless of the technology type, meeting the extra demands for engineering design, construction and/or supply chains may not be possible. The discussion focuses only on physical limitations of electricity generation, specifically around the timing and scale of retiring and/or replacing coal‐fired power generation capacity to meet the International Energy Agency's two‐degree scenario. We ignore the economics and politics of the transition scenarios and the transformation of the transportation and industrial sectors. What is clear is that the longer the delay in starting a significant transformation, the greater the challenge will become. Decision makers must understand the constraints to technology transitions to deliver effective policy. A broad international consensus is not required, instead reaching agreements and developing economically sustainable pathways to technology transitions in the United States, China, and India is more likely to be successful and the only means for significantly curbing global emissions. WIREs Energy Environ 2016, 5:33–48. doi: 10.1002/wene.177 This article is categorized under: Energy Systems Economics > Systems and Infrastructure Energy and Climate > Systems and Infrastructure Energy Policy and Planning > Systems and Infrastructure Energy Research & Innovation > Economics and Policy Abstract :